La Comunicación organizacional interna: Diferencias contextuales en los estudios realizados - Barzola Prado, Yaneth (2023)
The objective of the study was to identify the differences between studies conducted on internal organizational communication in the European, American and Latin American contexts; the literature review research analyzed 17 scientific articles published in high-impact databases. As a result, it was found that internal organizational communication is studied from a multidisciplinary approach, and the main approach used by Europe and the United States is the interpretative one, through the Symmetric Theory, which allows relating the concept of internal communication with new study variables. In conclusion, it was identified that the differences between the studies carried out on internal organizational communication in the European, American and Latin American contexts are mainly in the theoretical approach, with the interpretative paradigm predominating in the United States and Europe, while in Latin America the study is based on the functionalist paradigm. On the other hand, in the unit of analysis, research in the U.S. and European context integrates several organizations in the same investigation, in contrast to the Latin American context, in which the individual and isolated study of an organization predominates.